If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -384 = -6(8 + -8n) -384 = (8 * -6 + -8n * -6) -384 = (-48 + 48n) Solving -384 = -48 + 48n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-48n' to each side of the equation. -384 + -48n = -48 + 48n + -48n Combine like terms: 48n + -48n = 0 -384 + -48n = -48 + 0 -384 + -48n = -48 Add '384' to each side of the equation. -384 + 384 + -48n = -48 + 384 Combine like terms: -384 + 384 = 0 0 + -48n = -48 + 384 -48n = -48 + 384 Combine like terms: -48 + 384 = 336 -48n = 336 Divide each side by '-48'. n = -7 Simplifying n = -7
| 8(8+3x)=88 | | 102=8(1+6n)-2 | | 24+p=8 | | 3x-5(5x-3)=191 | | 4x-7x=4-25 | | 7m+4(m+6)=122 | | -8(6k+5)=248 | | -65.276=7.2(9c+1) | | -91=7v-7(6v-7) | | 49x=1/3 | | 4/6x=1/3 | | -249=-7(1+7v)+3 | | 26ab/13a | | 18x-41=3x-11 | | 6(4x-6)=132 | | 8*x-3/3x=2 | | -96=-6(6p+4) | | 4x-1=-16 | | (2x)+12=6-(4x) | | M-1/2_m-2/3=m-4/7 | | 0,5x=11 | | (2x)+12=(4x)-6 | | -12ab+8ab+7ab= | | 1/3*(3.14*7^2)*7 | | 1/3(3.14*7^2)7 | | (z-1)(2Z+3)=0 | | -6(-2n-6)=84 | | 5(e-7)=20 | | n^2=x | | (2x)+12=(4x)-12 | | y+3+7-9=90 | | u(x)=-2*300+1000 |